PERAMALAN LAJU INFLASI BULANAN KOTA PADANG MENGGUNAKAN METODE TRIPLE EXPONENTIAL SMOOTHING - Fitri, Aida; Anwar, Samsul; Zohra, Aja Fatimah; Nasution, Muhammad Haikal (Universitas Jambi, 2018)
The objective of this study is to predict the inflation rate (monthly) in Padang City for periods January 2018 to December 2020. In 2017, Padang City got an award as the city with the best TPID (Tim Pengendali Inflasi Daerah) performance in Indonesia followed by Kediri, Samarinda, Makassar and Ternate City. In order to help the TPID team in maintenance a low inflation rate, prediction of possible inflation that will be achieved in the following years is needed. Accordingly, the TPID team would have enough time to prepare several alternative actions to face an increasing inflation problem. We employ Triple Exponential Smoothing method, more known as Holt-Winters Exponential Smoothing to predict the inflation rate in Padang City. We build 6 tentative models with various parameter combinations and choose the one that has the lowest MSE and RMSE values as the final model. The final model has three parameters: Î±, Î² and Î³ with different values of 0.06, 0.08 and 0.33 respectively. Using this final model, we predict that the monthly inflation rate in Padang City for periods January 2018 to December 2020 would be in the interval in between -1 to 1 which is considered low. More detail, the inflation in 2018, 2019 and 2020 are predicted being in the interval in between -0.51 to 0.64, -0.72 to 0.42 and -0.94 to 0.21 respectively.